Impact of coronavirus 2019 pandemic on post-traumatic stress disorder symptoms among pregnant women in Jordan. (July 2022) - Bataineh, Mo'ath F; Mohamad, Maysm N; Al Dhaheri, Ayesha S; Rawashdeh, Monketh; Al-Nawaiseh, Ali M; Asali, Fida F; Hashim, Mona; Jarrar, Amjad; Abu Jamous, Dima O; Stojanovska, Lily; Daour, Rameez Al; Saleh, Sheima T; et al.
Objective: To examine the prevalence of psychological symptoms of the coronavirus disease 2019 outbreak among pregnant women and its association with gestational age and post-traumatic stress disorder symptoms. Methods: A cross-sectional study was conducted between June and November 2020 to assess the impact of the COVID-19 pandemic on mental health in pregnancy using the Impact of Event Scale-Revised. Pregnant women 18 years and older were recruited from antenatal and obstetrics clinics in Jordan. A total of 481 pregnant women participated in an online survey developed on Google Forms. A self-administered structured questionnaire was used to collect sociodemographic data, mental health information, and lifestyle changes. The Impact of Event Scale-Revised, the Perceived Support Scale, and the Mental Health Lifestyle Scale were administered. Variables related to sociodemographic information and dietary behavior and perception during the COVID-19 pandemic were also assessed. Results: The results showed that 58.6% of pregnant women reported the presence of post-traumatic stress disorder symptoms and women in the second trimester were more likely to show post-traumatic stress disorder symptoms compared with the first and third trimesters ( p  = 0.001). Moreover, a higher level of education, employment, poor dietary habits, and changes due to the pandemic were significantly associated with the Impact of Event Scale-Revised score and the presence of post-traumatic stress disorder symptoms. Conclusion: The COVID-19 pandemic was associated with high rates of psychological distress among pregnant women. Identifying mothers at risk of post-traumatic stress disorder symptoms may help improve maternity services and prevent adverse child outcomes.